MODEL PEMBERDAYAAN MASYARAKAT MELALUI DUKUNGAN SARANA PRASARANA (Kasus di Desa Cikiruh Wetan dan Paniis Kabupaten Pandeglang) - Dirlanudin Dirlanudin; Agus Sjafari; Kandung Sapto Nugroho; Ika Arinia Indriyany (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2018)
This research tries to identify and analyze condition of infrastructure in Cikiruh Wetan Village Cikeusik Subdistrict Pandeglang Regency represent coastal area bordering with Regency of Lebak and Paniis Village Koroncong Subdistrict represent agriculture area bordering with Regency of Serang and look for alternative of empowering rural community appropriate with existing potency. The fundamental problem is that infrastructure development in both villages is still low and uneven, in addition the villages are categorized as underdeveloped villages.The research aims to analyze the condition of infrastructure in the villages and formulate models of community empowerment through the support of infrastructure. This research uses qualitative approach with case study method. Using qualitative analysis with qualitative data and quantitative data. Informant determinated by purposive. Data Collection through Indepth Interview, observation and related documents.Theresearch results found that the condition of existing infrastructure in the research location, both education infrastructure, health, transportation, economy and settlements is still relatively inadequate. Infrastructure development policy has been implemented, but the way of its implementation is still less patterned and less integrated, especially for villages located in the area bordering with Lebak and Serang Regency. Village community empowerment efforts have been gradually undertaken, but not consistently and systematically implemented, especially the realization of infrastructure development in accordance with the potential and needs of villages, guidance and monitoring of the community to the maintenance and using the infrastructure reasonably.